Collecting rocks, gems and minerals : identification, values, lapidary uses - Polk, Patti (Krause Publications, a division of F+W Media, Inc., 2016)
Arranged by category and color of stone, provides values and tips for identifying, locating, buying, and collecting rocks, gems, and minerals.